Philosophical an histological assessment of diclofenac sodium on the liver of local rabbits (Journal of Pharmaceutical Negative Results, 2022)
The current Study was done to show the physiological and histological defect at different doses of diclofenac sodium on livers of Rabbits. Twenty rabbits was divided into four groups the therapiutic group (T) , over does group1 (T1), over dose group2 (T2) and control group each group was injected intraperitoneally by (2 , 20 , 50 mg/km) respectively and Distilled water, respectively for 14 days, at the fourteen day of experiment all animals were sacrificed, blood sample collected and liver was fixed immediately in 10% formalin for histological preparation and obtained serum for physiological test. There was no significant difference at the level of (0.05 <P) in the effectiveness of the Alanine aminotranseferase (ALT) and Aspartate aminotranseferase and gamma-glutamate transferase (GGT) in the serum of male rabbits in the T group and T1 group compared to the control group. Microscopic examination of the liver tissue in T group showed the presence of degeneration of hepatocytes and swelling of hepatocytes. showed edematous cells, infiltration of inflammatory cells in sinusoids in T1 group. In T2 group it showed colloid appearance in blood vessel, disappear of sinusoid, cell degeneration, degeneration of tunic cells of blood vessels.